ANALISIS SISTEM DISTRIBUSI DANA ZAKAT, INFAK, DAN SEDEKAH (ZIS)) PADA DOMPET DHUAFA CABANG SUMSEL BERDASARKAN TINGKAT MAQASHID SYARIAH - Ratna (Program Studi Perbankan Syariah, 2019)
This study raises the problem of (1) distribution of zakat, infaq & alms (ZIS) funds in 2014-2015 and (2) the distribution system of zakat, infaq & alms (ZIS) funds with maqashid sharia. Therefore, the purpose of writing this thesis is to analyze the distribution system of zakat, infaq and alms (ZIS) funds based on maqashid sharia. Thus, it can be seen that the distribution of zakat, infaq and alms funds and the compatibility between the distribution of zakat, infaq and alms funds with the maqashid of sharia. This research is a qualitative descriptive study. The type of research used is case research. The analysis used is a domain analysis with a semantic relationship pattern. The data used are secondary data in the form of ZIS fund collection data for 2013-2015 and the distribution of ZIS funds for 2014-2015. This paper concludes that the 2013 fund raised from the ZIS funds raised was IDR 2,961,064,212.00. The 2014 allocation of funds from the ZIS funds collected was IDR 3,637,750,450.00, while the funds that were distributed and realized in the Dompet Dhuafa programs in 2015 amounted to IDR 1,710,785,197.00. The results of the evaluation of the distribution of ZIS Dompet Dhuafa funds in the South Sumatra Branch can be concluded that the programs owned by the South Sumatra Branch of Dompet Dhuafa have been good in efforts to tackle poverty holistically both from religion, soul, mind, descent and wealth.